Comparison of the Effectiveness of Oral and Intravenous Antibiotics for the Treatment of Acute Sinusitis in Children at Skopje Hospital, Macedonia - Wilson, Bernadette; Antonio Wallace (Sriwijaya Journal of Otorhinolaryngology, 2024)
Introduction: Acute sinusitis is an infection of the sinus cavity that often occurs in children. Antibiotics are the primary therapy of choice for acute sinusitis, but the optimal route of administration remains a matter of debate. This study aims to compare the effectiveness of oral and intravenous antibiotics for the treatment of acute sinusitis in children at Skopje Hospital Macedonia. Methods: A retrospective cohort study was conducted on children aged 2-12 years diagnosed with acute sinusitis at Skopje Hospital Macedonia between 2019 and 2022. Patient data were collected from electronic medical records, including age, gender, symptoms, clinical findings, outcomes supporting examinations, and antibiotic therapy. Patients were grouped by route of antibiotic administration (oral vs. intravenous) and analyzed for comparison of treatment effectiveness. Results: A total of 200 children with acute sinusitis were included in this study. Of these, 100 children received oral antibiotics, and 100 children received intravenous antibiotics. The oral and intravenous groups did not show significant differences in demographic characteristics, symptoms, clinical findings, and results of investigations. The overall cure rate was 85% in the oral group and 90% in the intravenous group. This difference was not statistically significant (p=0.21). Subgroup analysis showed that oral antibiotics were as effective as intravenous antibiotics for children with uncomplicated acute sinusitis. Conclusion: Oral and intravenous antibiotics are equally effective for the treatment of acute sinusitis in children at Skopje Hospital Macedonia. Oral antibiotics can be used as a first-line therapy option for acute sinusitis in children, taking into account the safety profile, cost, and patient compliance.